Synthesis and characterization of aromatic polyamides containing an s-triazine ring with thiophenoxy linkages - Pal, R. R.; Patil, P. S.; Salunkhe, M. M.; Maldar, Noormahamad N.; Wadgaonkar, P. P. (Polymer International, 2005)
A series of aromatic polyamides containing an s-triazine ring with thiophenoxy linkages was synthesized from two new diacids, namely 2,4-bis-(4-carboxyphenoxy)-6-thiophenoxy-s-triazine and 2,4-bis-(3-carboxyphenoxy)-6-thiophenoxy-s-triazine, and commercially available aromatic diamines by using Yamazaki's phosphorylation reaction. The polyamides were obtained in good yields and were characterized by solubility tests, viscosity measurements, FTIR, H-1 and C-13 NMR spectroscopy, X-ray diffraction studies and thermogravimetric analysis. The polyamides were found to have inherent viscosities in the range of 0.35 to 0.56 dl g(-1) in N,N-dimethylacetamide (DMAc) at 30 +/- 0.1 degreesC. All the polyamides were readily soluble in solvents such as DMAc, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF) and m-cresol. Thermogravimetric analysis of the polyamides indicated no weight loss below 345 degreesC under a nitrogen atmosphere. (C) 2004 Society of Chemical Industry.
Keywords: 2; 4-bis-(3/4-carboxyphenoxy)-6-thiophenoxy-s-triazine; direct polycondensation; polyamide; s-triazine ring

Synthesis, structure, electrochemistry and ROMP-activity of new ferrocenyl analog of Grubbs' metathesis catalyst - Maishal, T. K.; Mondal, Biplab; Puranik, Vedavati G.; Wadgaonkar, P. P.; Lahiri, Goutam Kumar; Sarkar, A. (Journal of Organometallic Chemistry, 2005)
Treatment of [(PCy3)(2)Cl2Ru=CH-Ph] (1) with vinylferrocene 1 and 1-ferrocenyl-1,3-butadiene 2 yielded solid products. These new complexes were characterized by H-1 NMR, P-31 NMR and C-13 NMR spectroscopy. X-ray crystal structures of both the complexes have been solved. The crystal structure of II confirmed the assigned structure and revealed existence of two sets of intermolecular C-H-Cl(M) type interactions, viz. (Ru)Cl-H-C(ferrocene) and (Ru)Cl-H-CHCl2. The air-stable, dark solid II is all efficient catalyst for ring-opening metathesis polymerization (ROMP) of cyclopentene, norbornene and cycloocta-1,5-diene. Electrochemical behavior of the complexes clearly reflects electronic communication between two metal centers. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Electrochemistry; ferrocene; Metathesis; non-covalent interactions; ring-opening metathesis polymerization; ruthenium carbene

Synthesis and characterization of novel hydrophobically end-capped poly(ethylene oxide)s [PEOs] - Badiger, Manohar V.; Kadam, Vijay S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique (Macromolecular Symposia, 2006)
We report on the synthesis and characterization of a novel hydrophobically modified end-capped poly(ethylene oxide)s. The end-capping agent of this polymer was designed and synthesised from a renewable resource material namely, gallic acid (i.e. 3,4,5-trihydroxybenzoic acid), the byproduct of tannin industry. The hydroxyl groups at 3, 4 and 5 positions of gallic acid provide an opportunity for varying the hydrophobicity of the compound. The hydrophobic end-capping compound, 3,4,5tridodecyloxy bezoylazide was prepared from gallic acid and PEGS with different chain lengths (of number average molecular weights, 10000 and 35000 g/mol) were endcapped. using 3,4,5-tridodecyloxybenzoyl azide. The quantitative analysis of end-capping in the polymers was demonstrated by H-1-NMR spectroscopy and the rheological studies were carried out in the surfactant solutions.
Indo-French Symposium on Fibrillar Networks as Advanced Materials, Inst Charles Sadron, Strasbourg, FRANCE, SEP 21-23, 2005
Keywords: end-capped PEOs; hydrophobically modified polymers; water-soluble polymers

Sulfamic acid: an efficient and cost-effective solid acid catalyst for the synthesis of alpha-aminophosphonates at ambient temperature - Mitragotri, Satish D.; Pore, D. M.; Desai, Uday V.; Wadgaonkar, P. P. (Catalysis Communications, 2008)
Sulfamic acid catalyzed solvent-free protocol has been developed for the synthesis of alpha-aminophosphonates by three component condensation between aldehydes, amines and diethyl phosphite at ambient temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aminophosphonates; diethylphosphite (DEP); solid acid catalyst; Solvent-free; sulfamic acid (SA)

Solvent extraction of trivalent indium from succinate solution by 2-octylaminopyridine in chloroform - Mahamuni, Sandip V.; Kolekar, S. S.; Wadgaonkar, P. P.; Anuse, Mansing A. (Journal of the Iranian Chemical Society, 2009)
Extraction processes of indium(III) with 2-octylaminopyridine (2-OAP) from media of various complexing ability, succinate and salicylate, in chloroform have been elucidated. The ion-pair complex has also quantitative extraction in xylene and 1,2-dichloroethane. Indium(III) from organic phase was stripped with 1.0 M hydrochloric acid and determined complexometrically with EDTA. The stoichiometry of the extracted species was found out on the basis of slope analysis. The extraction of indium(III) proceeds by an anion exchange mechanism and the extracted species is [RR'NH(2)(+)In(succinate)(2)(-)]((org)). Temperature dependence of the extraction equilibrium constant was also examined to estimate the apparent thermodynamic functions (Delta H, Delta G and Delta S) for extraction reaction. It is possible to separate indium(III) from Zn(II), Cd(II), Pb(II), Hg(II), Bi(III), Tl(I), Tl(III), Ga(III), Al(III), Te(IV), Se(IV), Sb(III), Fe(III) and Sn(IV). The method is simple, rapid and reproducible and can be used to determine the indium from samples like alloys.
Keywords: 2-OAP; Binary separations; Indium(III); liquid-liquid extraction; Sodium succinate

Synthesis and properties of new polybenzoxazines containing (substituted) cyclohexyl moieties - Kumar, K. S. Santhosh; Nair, C. P. Reghunadhan; Ninan, K. N.; Kulkarni, A. D.; Wadgaonkar, P. P. (Polymers for Advanced Technologies, 2009)
A series of new polybenzoxazines were synthesized based on diphenols containing (substituted) cyclohexyl moiety and were characterized by FT-IR, (1)H-NMR, and (13)C-NMR spectroscopy. These new benzoxazine monomers exhibited better processability with lower peak cure temperature and a wide cure controllable window (CCW) as manifested in differential scanning calorimetric analysis. The cure analysis was performed by FT-IR spectroscopy. Glass transition temperature of new polybenzoxazines varied from 170 to 205 degrees C. The cyclohexyl bridge groups facilitated ring opening, resulting in polymer with improved thermal stability in comparison to bisphenol A-based benzoxazine as assessed by the various thermal analyses. The water contact angles of polybenzoxazines containing (substituted) cyclohexyl moieties were higher than that of bisphenol A-based polybenzoxazine, implying their higher hydrophobicity. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: Hydrophobicity; polybenzoxazines; thermally stable polymers

Synthesis and thermal properties of soluble silicon containing phenylated aromatic-aliphatic polyamides - Ghanwat, A. A.; Sayyed, M. M.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Journal of Thermal Analysis and Calorimetry, 2009)
Aromatic polyamides find many applications in diverse and critical areas due to their high thermal stability coupled with high mechanical properties. However most of such aramides are difficult to fabricate because of their limited solubility and high melting temperature. Improvements in processability have been reported by incorporating bulky pendant groups and aliphatic spacer groups. Similarly to improve the solubility of polymers approaches of incorporating silicon in main polymer chain and co-polymerization techniques were useful. We report the synthesis and characterization of a series of phenylated silicon containing aromatic-aliphatic polyamides from a mixture of 2, 5-bis (4-carboxy methylene phenyl)-3, 4-diphenyl thiophene (CMPDT) and bis-(4-carboxy phenyl) dimethyl silane (BCPDS) in various mole proportions, with commercial aromatic diamine. Thus a series of novel co-polyamides having pendant phenyl groups, methylene spacer and silicon moiety was prepared by judicious combination of (CMPDT); BCPDS and aromatic diamine; bis-(4-aminophenyl) ether (ODA), by direct polycondensation using Yamazaki's phosphorylation method. These high molecular mass polyamides were obtained in high (89-98%) yields and had viscosities in the range of 0.23-0.57 dL/g in DMAc. Polyamides showed improved solubility in polar aprotic solvents, like NMP, DMAc, DMSO and DMF; had high thermal stability; with no mass loss below 335 A degrees C.
Keywords: 2; 4-diphenyl thiophene; 5-bis (4-carboxy methylene phenyl)-3; bis-(4-amino phenyl) ether; bis-(4-carboxy phenyl) dimethyl silane; Copolyamides; solubility; thermal stability

Synthesis and characterization of novel aromatic-aliphatic polyamides from bis-[(4-aminobenzyl)-4-benzamide] ether - Patil, A. S.; Medhi, M.; Sadavarte, Nilakshi V.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A novel aromatic diamine monomer containing preformed aromatic-aliphatic amide and ether linkage, bis-[(4-aminobenzyl)-4-benzamide] ether (BABE) was prepared from 2-phenylacetonitrile. BABE was characterized by FT-IR, (1)H NMR, (13)C NMR and mass spectrometry. Five new aromatic polyamides were prepared by low temperature solution polymerization from BABE and different mole proportions of isophthaloyl chloride (IPC) or terephthaloyl chloride (TPC). The resulting polymers were characterized by means of FT-IR, inherent viscosity [eta(inh)], solubility, differential scanning calorimetry [DSC], thermogravimetric analysis [TGA] and X-ray diffraction [XRD]. Polyamides were obtained in good yields and had moderate to high molecular weights as indicated by inherent viscosities in the range 0.63-1.35 dL/g in (DMAc + 4% LiCl). XRD results showed the partly crystalline nature of polymers and these polymers dissolved in aprotic polar solvents containing LiCl. The solubility of copolyamides improved due to random placement of constituent IPC and TPC during polymerization. DSC analysis of these polyamides showed glass transition temperatures in the range of 197-204 degrees C, and they showed no weight loss below 336 degrees C when analyzed by TG. These polyamides have potential applications as engineering materials. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: Bis-[(4-aminobenzyl)-4-benzamide] ether; ether linkage; Inherent viscosity; polyamides; thermal stability; XRD

Synthesis and characterization of polyesters from 2,3-bis (4 `-hydroxy phenyl) quinoxaline and 2,3-bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline - Patil, V. B.; Medhi, M.; Bhairamadgi, Nagendra S.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
Two bisphenols containing pendant, quinoxaline moiety; 2,3-bis (4'-hydroxy phenyl) quinoxaline (BHPQ) and 2,3-bis (2'-hydroxynaphthalene-6-yl) quinoxaline (BHNQ) were synthesized and characterized by FT-IR, (1)H, (13)C NMR and mass spectrometry. Aromatic polyesters and copolyesters were prepared by interfacial polymerization from BHPQ or BHNQ and isophthaloyl chloride or terephthaloyl chloride or a mixture of different mole proportions of (IPC + TPC). These polyesters and copolyesters were characterized by spectroscopic technique, viscosity measurement, solubility, thermal stability. DSC and XRD. Polymers had moderate to high molecular weights as evidenced by the inherent viscosities in the range 0.35-0.78 dL/g for BHPQ series and 0.27-0.52 dL/g for BHNQ series. BHPQ polyesters and copolyesters dissolved in m-cresol, NMP and conc. H(2)SO(4) whereas, BHNQ polyesters and copolyesters were readily soluble in NMP, DMAc, (TCE + phenol) and partly soluble in solvent like CHCl(3), pyridine, etc. Wide angle X-ray diffraction (WAXD) results showed that introduction of quinoxaline moiety into polymer chain and aromatic phenyl/rigid naphthyl structures lead to crystalinity. Differentional scanning calorimetry of BHNQ polyesters showed the glass transition temperatures in the range of 131-151 degrees C. BHPQ polyesters did not show any weight loss below 330 degrees C and retained 27-55% weight at 900 degrees C when investigated by TGA under nitrogen atmosphere demonstrating good thermal stability BHNQderived polyesters showed initial decomposition temperatures in range 211-234 degrees C. The structure-property relationships for the mentioned polyesters are analyzed, as these polyesters are of interest as materials for electronics, microelectronics and membrane separation. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: 2; 3-Bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline; 3-Bis (4 `-hydroxy phenyl) quinoxaline; Aromatic polyesters; Glass transition temperature; solubility; Thermal properties